A review of anthropological approaches to ageing - Kaczmarek, Maria; Szwed, Anita (Polskie Towarzystwo Antropologiczne, 1997)
It is evident that the pattern of ageing among humans has a unique character. Therefore, when undertaking any research on human ageing one has to specify a proper methodology and methods which are available in the anthropological perspective. The paper is aimed at providing a review of anthropological approaches to the study of ageing. On the basis of the meaning and scope of the concept of ageing, its sources and causal factors are discussed. Further, functional, physiological and morphological indicators of ageing are briefly described. Much attention is focused on the concept of biological age which is the key notion for assessment of variation in the rates of human ageing.